2017
DOI: 10.1186/s13028-017-0288-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of subclinical mastitis in Finnish dairy cows: changes during recent decades and impact of cow and herd factors

Abstract: BackgroundThe dairy industry has undergone substantial structural changes as intensive farming has developed during recent decades. Mastitis continues to be the most common production disease of dairy cows. Nationwide surveys of mastitis prevalence are useful in monitoring udder health of dairy herds and to study the impact of structural changes on the dairy industry. This survey on bovine subclinical mastitis was the first based on cow composite milk somatic cell count (SCC) data from the Finnish national hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 35 publications
6
32
1
3
Order By: Relevance
“…For example, a study in the United States determined that cows kept in tiestalls had a 1.5 times greater risk than those housed in freestalls (Richert et al, 2013), confirming a previous Norwegian study (Valde et al, 1997). Nevertheless, this finding was not observed in the current study, although 34% of farms in this study population had tiestalls, which corresponds with findings on Finnish dairy farms, where cows kept in freestalls with automated milking systems or with milking parlors were reported to have a higher estimated SCC than cows kept in tiestalls (Hiitiö et al, 2017). Overall, herd size (median = 21 cows; mean = 26.9 cows in this study population) did not appear to have a substantial influence on the probability of mastitis occurring according to the statistical model applied here.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For example, a study in the United States determined that cows kept in tiestalls had a 1.5 times greater risk than those housed in freestalls (Richert et al, 2013), confirming a previous Norwegian study (Valde et al, 1997). Nevertheless, this finding was not observed in the current study, although 34% of farms in this study population had tiestalls, which corresponds with findings on Finnish dairy farms, where cows kept in freestalls with automated milking systems or with milking parlors were reported to have a higher estimated SCC than cows kept in tiestalls (Hiitiö et al, 2017). Overall, herd size (median = 21 cows; mean = 26.9 cows in this study population) did not appear to have a substantial influence on the probability of mastitis occurring according to the statistical model applied here.…”
Section: Discussionsupporting
confidence: 78%
“…Similar findings have been reported in other studies of udder health in small dairy farms. For example, a Finnish study (largest herd size category: >60 cows) reported average herd size as having no effect on subclinical mastitis (OR = 1.003), whereas a Swiss study found that a herd size of >27 dairy cows and heifers increased the odds of subclinical mastitis occurring compared with smaller herds (<20 head; Doherr et al, 2007;Hiitiö et al, 2017). Dairy farms in other European countries often have much larger herds, with surveys from 2016 to 2017 reporting a mean of 61.9 cows per herd in Germany, 93.8 cows per herd in the Netherlands, and 146 cows per herd in the United Kingdom compared with just 21.3 cows per herd in Austria at that time (Barkema et al, 2015;AHDB Dairy, 2018;BMEL Statistik, 2018;CRV, 2018;ZAR, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although the milk appears normal, cows with subclinical mastitis will produce less milk, and the quality of the milk will be reduced. In addition, infected cows can be a source of infection to other animals in the herd (Hiitiö et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cows with a high SCC indicative of subclinical mastitis have an estimated loss in milk production of more than 1,500 pounds per cow (Kirkpatrick & Olson, ). Healthy milk (HM) has lower cell counts ranging from 50,000 to 200,000 cells/ml of milk (Hiitiö et al., ). However, the cell counts of milk from cows with SCM can reach a few million cells per millilitre and usually range from 200,000 to 500,000 cells/ml (Guan, Wu, Xu, Su, & Hu, ; Smith, ; Sun et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…cow, diagnosis, S100A12, subclinical mastitis 50,000 to 200,000 cells/ml of milk (Hiitiö et al, 2017). However, the cell counts of milk from cows with SCM can reach a few million cells per millilitre and usually range from 200,000 to 500,000 cells/ml (Guan, Wu, Xu, Su, & Hu, 2017;Smith, 1996;Sun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%